2005
DOI: 10.1158/1055-9965.epi-04-0376
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptive Use and Risk of Early-Onset Breast Cancer in Carriers and Noncarriers of BRCA1 and BRCA2 Mutations

Abstract: Background: Recent oral contraceptive use has been associated with a small increase in breast cancer risk and a substantial decrease in ovarian cancer risk. The effects on risks for women with germ line mutations in BRCA1 or BRCA2 are unclear. Methods: Subjects were population-based samples of Caucasian women that comprised 1,156 incident cases of invasive breast cancer diagnosed before age 40 (including 47 BRCA1 and 36 BRCA2 mutation carriers) and 815 controls from the San Francisco Bay area, California, Onta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 37 publications
4
76
1
9
Order By: Relevance
“…Two recent studies based on early-onset breast cancer cases, including small numbers (o100) of carriers, found no general increase in breast cancer risk with OC use. One study found increased breast cancer risk only with teenage (o20 years) OC use (OR ¼ 1.53 (95% CI 1.17 -1.99) per year of use at age o20 years) (Jernstrom et al, 2005), and in the others there was even a suggestion of decreased breast cancer risk within BRCA1 carriers (OR ¼ 0.22, 95% CI 0.1 -0.49 for OC use of at least 1 year) (Milne et al, 2005). Altogether, these studies suggest that for breast cancer risk, OC have similar relative effects in carriers and non-carriers.…”
Section: Hormonal Exposures -Oral Contraceptives (Oc)mentioning
confidence: 98%
“…Two recent studies based on early-onset breast cancer cases, including small numbers (o100) of carriers, found no general increase in breast cancer risk with OC use. One study found increased breast cancer risk only with teenage (o20 years) OC use (OR ¼ 1.53 (95% CI 1.17 -1.99) per year of use at age o20 years) (Jernstrom et al, 2005), and in the others there was even a suggestion of decreased breast cancer risk within BRCA1 carriers (OR ¼ 0.22, 95% CI 0.1 -0.49 for OC use of at least 1 year) (Milne et al, 2005). Altogether, these studies suggest that for breast cancer risk, OC have similar relative effects in carriers and non-carriers.…”
Section: Hormonal Exposures -Oral Contraceptives (Oc)mentioning
confidence: 98%
“…A population-based case-control study assessed COC use as a risk factor in Caucasian carriers and noncarriers of BRCA1 and BRCA2 mutations. 23 Use of low-dose COCs was not associated with increased risk of breast cancer in either BRCA2 mutation carriers or noncarriers. Furthermore, the results suggested a reduced risk of breast cancer in BRCA1 mutation carriers.…”
Section: -12mentioning
confidence: 90%
“…Notably, of the cases that used OCP in this study, more than 50% initiated OCP use before 1975, when the estrogen content of OCP was substantially higher than current formulations. However, a large multinational case-control study including 1156 breast cancer cases diagnosed under age 40 (of which 47 were BRCA1 carriers and 35 BRCA2 carriers) as well as 815 controls, did not demonstrate an increased risk of OCPassociated breast cancer (Milne et al, 2005). In fact, a decrease in breast cancer risk was seen in BRCA1 carriers using OCP for >12 months (OR 0.22, 0.10-0.49).…”
Section: Chemoprevention Of Ovarian Cancermentioning
confidence: 93%